INSTITUTIONAL MECHANISMS FOR IMPROVING THE INVESTMENT CLIMATE IN THE NATIONAL ECONOMY (Symposium on Life and Environmental Sciences, 2026)
In the conditions of modern global economy, the quality of investment climate is one of the main factors determining the level of economic development of each country. In particular, attracting investments, their effective placement and obtaining the maximum economic efficiency in the national economy is largely determined by the institutional foundations of the investment climate. In this regard, the improvement of institutional mechanisms for improving the investment climate is today as an urgent scientific and practical challenge.Investment climate refers to a set of economic, legal, political and social conditions created for investors. The quality level of this environment plays a crucial role for investment decisions. Especially for foreign investors, presence of a stable and reliable institutional system reduces the risk of investment and increases the investment attractiveness.